Effect of pre-cooling injection site on pain perception in pediatric dentistry: "A randomized clinical trial" - Faezeh Ghaderi; Shahin Banakar; Shima Rostami (Wolters Kluwer Medknow Publications, 2013)
Background: Injection of local anesthesia is one of the most important reasons for development of avoidance behavior in children. Efforts have been performed to decrease pain perception of injection. The present research evaluated the effect of cooling the injection site on pain perception before infiltration of local anesthetics. Materials and Methods: A prospective single-blind crossover clinical trial was used to investigate pain perception in 50 healthy pediatric patients who needed bilateral buccal infiltration of local anesthetics for dental treatment. They received a topical anesthetic agent (Benzocaine) on one side (control) for 1 min and topical anesthetic agent plus one minute of ice pack on the other side (trial) prior to the injection. A dentist blind to the study assessed the patients' reaction during injection. Wilcoxon and Mann-Whitney U tests were used for statistical analysis. Statistical significance was defined at P < 0.05. Results: The means of sound, eye, and motor scales (SEM) were 4.06 ± 1.32 and 5.44 ± 1.79 for the study and control groups, respectively. The means of visual analogue scales (VAS) for the study and control groups were 42.20 ± 12.70 and 58.40 ± 16.83, respectively; with statistically significant differences between the two groups (P < 0.05). Conclusion: Cooling the injection site before infiltration of local anesthetics in the buccal mucosa for 1 min, reduced pain perceived by pediatric patients.